The implementation of parking policy in Cirebon City Kejaksan Square - Khofifah, Khofifah; Toyibah, Siti; Zulkarnaen, Iskandar; Andriany, Dian (Indonesian Journal of Multidisciplinary Science, 2024)
Kejaksan Square has become a tourist attraction in Cirebon City since it was renovated in April 2021. However, the implementation of parking policies there still faces obstacles such as lack of public awareness, lack of commitment of officers in socializing parking rules, and lack of adequate parking infrastructure. This study aims to evaluate the implementation of parking implementation policies in the Cirebon City Kejaksan Square. Qualitative and descriptive research methods are used, by collecting data through observations, interviews, and documentation. Edwards III's theory of policy implementation is used as a theoretical framework. The results showed that communication, resources, disposition and bureaucratic structure affect the implementation of parking policies. Despite the obstacles, the active role of the Department of Transportation and the availability of adequate resources provided support for the success of the policy. The ultimate goal is to improve the quality of public facilities and infrastructure services that are environmentally friendly.